Demographic and background factors influencing online shopping in South Africa - Munonde, Andani (My University, 2018)
Abstract As technology vastly becomes an essential component of our daily lives, Businesses are fast adopting online platforms which enable them to i.e. communicate and receive immediate feedback from consumers and offer a different kind of shopping experience through online shopping. In South Africa, online shopping is beginning to increase its presence and at the same time more South Africans are becoming exposed to the Internet. Therefore, it is becoming increasingly vital for Businesses to understand what characteristics influence a consumer’s behaviour for online shopping. In addition to this, the increase in online sales has created an interest for retailers to understand what factors influence consumers to shop online (Clemes, Gan, & Zhang, 2014). Previous researchers have also indicated that more awareness is required around the various elements which contribute towards the complexity regarding the online shopping experience. This study evaluated race and age demographic elements to determine whether the country’s historical background has an influence on the Internet proficiency, which may in turn influence online shopping. The influence of cost of data on online shopping was also evaluated. A quantitative approach was applied in this study; hence, a questionnaire was used as a data collection method. The data was analysed using the statistical hypothesis testing. The key finding discovered from the study was that given the high cost of data in South Africa, affordability of data does not influence a consumer’s behaviour to make online purchases. Although elements such as time and money saving have no influence in the cost of data being a reason to shop online, these elements present an interesting dynamic in terms of additional functionalities that businesses could add to their online platforms to further increase their consumer base. Future researchers should consider undertaking studies that focus on specific industries in order to explore various impacts per industry.
MBA Thesis
Keywords: Consumer behavior, Teleshopping, Internet marketing -- South Africa.